Problematics of Inter-Regional Cooperation in Indonesia - Muhammad Fauzan; Dwiyanto Indiahono; Riris Ardhanariswari (Sriwijaya Law Review, 2024)
This article aims to identify the problems of implementing inter-regional cooperation from the widest possible autonomy perspective. This becomes important because cooperation between regions seems to run well shortly after policies in the form of laws and government regulations are enacted. However, in regional cooperation, many problems lurk and can lead to the failure of cooperation between regions. This research is legal research using a statute approach, a conceptual approach, and a historical approach. This research method and approach are appropriate to explain the problematic phenomenon of cooperation between regions in Indonesia based on Law No. 23 of 2014 concerning Regional Government. Based on the results of preliminary research, several problems arise in the implementation of regional cooperation, especially cooperation between regions, including the following: First, cooperation between regions whose object is related to income sharing often experiences difficulties in its implementation, especially in determining the amount of income/profits for each region; Second, the emergence of regional egoism, especially in the cooperation between the Parent Region and the regions resulting from the expansion; Third, the lack of data and information about the object of cooperation that has the potential to be better if implemented through cooperation between regions that are geographically close together; Fourth, the lack of initiation to carry out cooperation between regions due to the mindset of each region to deal with internal affairs only; and Fifth, no institution/agency specifically handles inter-regional cooperation.